Navigating Future Management and Ownership of Health Data in 2050, Finland with a Special Focus to the General Data Protection Regulation (GDPR) - Rahman, Shahriar (My University, 2025)
The growing digitalization of healthcare systems has brought about a transformation in the administration and ownership of health data, which has the potential to provide opportunities and challenges that have never been seen before. The impact of the General Data Protection Regulation (GDPR) and national legislative frameworks is the primary subject of this thesis, which investigates the future of health data governance in Finland from the year 2050 onward. The study investigates the ways in which technology breakthroughs, legislative developments, and sociological trends interact with one another on the basis of a combination of the Legal Doctrinal Method and the Multi-Level Perspective (MLP) framework. Key findings show major gaps in existing legal frameworks, particularly in defining ownership rights for data created by smart medical devices and processed by artificial intelligence (AI). These loopholes are particularly problematic because they are not adequately addressed. Explicit ownership rights, better regulation of AI-driven data monetization, and improved interoperability frameworks that are compatible with GDPR are the three crucial areas that are identified in the thesis as needing reform the most. To illustrate the various paths that health data governance can take, various scenarios for the year 2050 foresee opposing futures. These possibilities range from an ecosystem driven by patients to a model dominated by industry. Legal reforms, rigorous regulation of artificial intelligence, and collaborative tactics between public and commercial stakeholders are some of the recommendations made in the thesis in order to overcome these difficulties. By taking these steps, Finland will ensure that it continues to be a global leader in the management of health data that is ethical, equitable, and innovative. This will ensure that individual rights are balanced with the benefits to society.